Living systematic reviews in a context of rapidly emerging diseases: challenges and lessons learned. (20th October 2021) - Iannizzi, C; Dorando, E; Burns, J; Weibel, S; Dooley, C; Wakeford, H; Estcourt, LJ; Skoetz, N; Piechotta, V
Abstract: Background: In a context of a rapid emerging disease, like the COVID-19 pandemic, we are confronted with clinical uncertainty, evolving epidemiological setting and lacking evidence. Within the context of such a high-priority topic, living systematic reviews (LSRs) are an important systematic review type characterized through regular updating and permanent surveillance of continuously evolving evidence. However, with the new pandemic-related challenges, the standard LSR methodology had to be adapted. Objectives: The objective is to discuss certain challenges that occurred when conducting LSRs in a rapidly emerging disease context. In particular, we give insights in the lessons we have learned from the conduct of two COVID-19 LSRs and highlight emerging methodological aspects. Results: With the evolving knowledge around the virus and its caused disease, we learned that the initial plan for inclusion of study designs, publication types, interventions and comparators, outcomes and the search strategy had to be adapted. The author teams for example had to revise outcome measures or included observational data in addition to evidence from randomized controlled trials, as they provided substantial information on the safety of investigated interventions. For deciding when to update a LSR, additional aspects, such as policy relevance or waiting for important evidence dependent on the individual research question were considered. To avoid biases in the review process, we learned that transparent reporting of any methodological adaptations is highly relevant; between protocol and review, as well as between each review update. Conclusions: Our experience showed that LSRs are highly suitable in a pandemic context, in particular when facing unexpected methodological and clinical challenges. The research question, study designs and the methodology, should be revisited and critically discussed before each update, to be flexible enough for addressing the pandemic context. Key messages: Living systematic reviews are highly relevant in a pandemic context, but the methodology and decision when to update the review have to be adapted to respond purposeful to the emerging topic. To avoid biases in the review process, we learned that transparent reporting of any methodological adaptations is highly relevant; between protocol and review, as well as between each review update.